Divine violence in the Book of Samuel - Gilmour, Rachelle (Oxford scholarship online, 2021)
Much of the drama, theological paradox, and interpretive interest in the Book of Samuel in the Hebrew Bible derives from instances of God's violence in the story. In 'Divine Violence in the Book of Samuel', Rachelle Gilmour explores these narratives of divine violence from ethical, literary and political perspectives, in dialogue with the thought of Immanuel Kant, Martha Nussbaum and Walter Benjamin. Gilmour asks, is the God of Samuel a capricious God with a troubling dark side, or can fresh approaches, grounded in the text's historical contexts, throw light on these startling and often incomprehensible acts of God?